Feasibility of FitSurvivor: A technology‐enhanced group‐based fitness intervention for adolescent and young adult survivors of childhood cancer. Issue 9 (26th June 2020) - Devine, Katie A.; Viola, Adrienne; Levonyan‐Radloff, Kristine; Mackowski, Nicholas; Bozzini, Brittany; Chandler, Alexa; Xu, Baichen; Ohman‐Strickland, Pamela; Mayans, Sherri; Farrar‐Anton, Anne; Sahler, Olle Jane Z.; Masterson, Margaret; et al.
Abstract: Background: This study evaluated the feasibility of a technology‐enhanced group‐based fitness intervention for adolescent and young adult (AYA) survivors of childhood cancer. Procedure: AYA survivors ages 13‐25 years were randomized to the intervention (eight in‐person group sessions with mobile app and FitBit followed by 4 weeks of app and FitBit only) or waitlist control. Assessments were at 0, 2, 3, 6, and 9 months. Feasibility was evaluated by enrollment, retention, attendance, app engagement, and satisfaction. Secondary outcomes included physical activity, muscular strength/endurance, cardiorespiratory fitness, health‐related quality of life, and fatigue. Results: A total of 354 survivors were mailed participation letters; 68 (19%) were screened, of which 56 were eligible and 49 enrolled (88% of those screened eligible, 14% of total potentially eligible). Forty‐nine survivors ( M age  = 18.5 years, 49% female) completed baseline assessments and were randomized (25 intervention, 24 waitlist). Thirty‐seven (76%) completed the postintervention assessment and 32 (65%) completed the final assessment. On average, participants attended 5.7 of eight sessions (range 1‐8). Overall intervention satisfaction was high ( M  = 4.3, SD = 0.58 on 1‐5 scale). Satisfaction with the companion app was moderately high ( M  = 3.4, SD = 0.97). The intervention group demonstrated significantly greater improvement in lower body muscle strength compared to the waitlist postintervention, and small but not statistically significant changes in other secondary measures. Conclusions: A group‐based intervention with a mobile app and fitness tracker was acceptable but has limited reach due to geographical barriers and competing demands experienced by AYA survivors.